2015
DOI: 10.1111/jvh.12471
|View full text |Cite
|
Sign up to set email alerts
|

Costs and outcomes of treating chronic hepatitis C patients in routine care – results from a nationwide multicenter trial

Abstract: Viral hepatitis is a major public health problem affecting millions of people worldwide. Long-term consequences are the development of liver cirrhosis and hepatocellular carcinoma. The aim of the study was to assess outcomes and costs of treating patients with chronic hepatitis C in clinical practice in Germany. We carried out a prospective noninterventional study. Information on treatment outcomes, resource utilization and quality of life was provided by 281 physicians throughout Germany. Data of 3708 monoinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…Regarding the results of our chart review, numerous studies in other countries have demonstrated similar findings, with antiviral drugs accounting for the majority of treatment costs 13,15,27–29. However, they estimate that antiviral costs would amount to around 75–85% of total costs, which is lower than our calculation of 92%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding the results of our chart review, numerous studies in other countries have demonstrated similar findings, with antiviral drugs accounting for the majority of treatment costs 13,15,27–29. However, they estimate that antiviral costs would amount to around 75–85% of total costs, which is lower than our calculation of 92%.…”
Section: Discussionsupporting
confidence: 80%
“…Several cohort studies performed in Germany and North America have looked at costs and MRU associated with dual and triple IFN-based therapy in routine clinical care 1316…”
Section: Introductionmentioning
confidence: 99%
“…These cost parameters include drugs, diagnostic procedures, and treatment, including treatment of side effects [18]. The costs applied for diagnostic procedures are based on Stahmeyer et al [23]. The costs per disease statuses were derived from published literature [24][25][26].…”
Section: Assumptions For Health State Costsmentioning
confidence: 99%
“…16-wöchige Therapie SVR-Raten von 88 % respektive 86 %[43]. Versorgung für die Dualtherapie mit PegIFN und RBV veröffentlicht[45].Bis zur Einführung der Kombinationstherapien mit Sofosbuvir wurde die Dualtherapie als Standardtherapie für die Genotypen 2 -6 empfohlen [6]. Die Analyse zeigt, dass die durchschnittlichen Kosten pro SVR für therapienaive Patienten bei 21 667 €/SVR für den Genotyp 2 und 22 218 €/SVR für den Genotyp 3 betragen.…”
unclassified